Intertidal Environmental Chamber: An automatic system to accurately simulate the thermal complexity of intertidal environments - Luís F. Pereira; Rui Seabra; Bruno Loureiro; Francisco Arenas; Fernando P. Lima (Methods in Ecology and Evolution)
Abstract Climate change is increasing the frequency of extreme temperature events, often causing sublethal stress or mass mortalities in organisms. This has raised the interest in assessing species' thermal performance under current and future climates. Common‐garden experiments are widely used to assess species' heat tolerance across populations from different origins under standardised conditions. Replicating realistic conditions, especially for intertidal environments, where both marine and terrestrial stressors are involved, is technically challenging. Consequently, ecologists often develop custom‐built systems that are either too simplistic (e.g. ignoring emersion) or difficult to replicate, leading to inconsistencies between studies. To address this challenge, we developed the Intertidal Environmental Chamber: a modular, open‐source system designed to realistically simulate the complex thermal environment of intertidal habitats with independent control of tides, immersion and emersion temperatures, light intensity and water exchange. Here, we showcase the system's capabilities and evaluate its accuracy in replicating field data. We also offer recommendations for running long‐term, remote‐controlled, geographically distributed and synchronised experiments.